Erythroid colony formation from human fetal liver. - Rowley, P T (1978)
The liver of the human fetus, induced to abort by prostaglandin or by hypertonic saline, contains cells that form colonies in methylcellulose in vitro. The colonies are erythroid as identified by cellular staining of hemoglobin by benzidine. Colony formation is generally similar, with regard to number, size and time of development, to that observed in cultures of nonadherent cells from human adult marrow. The number of colonies observed increases with the concentration of erythropoietin used and with the concentration of cells plated and decreases with the time interval between intra-amniotic instillation of the inducing agent and culture. Colong number is not greatly influenced by fetal age in the period 16-20 weeks or by whether the inducing agent is prostaglandin or hypertonic saline. Prostaglandin- and hypertonic saline-induced abortuses thus provide an abundant source of human fetal erythroid tissue for morphologic and biochemical studies of erythroid development.